2016
DOI: 10.1158/0008-5472.can-15-2443
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Subtypes of Gastric Cancer Defined by Molecular Characterization Include Novel Mutational Signatures with Prognostic Capability

Abstract: Gastric cancer is not a single disease, and its subtype classification is still evolving. Next-generation sequencing studies have identified novel genetic drivers of gastric cancer, but their use as molecular classifiers or prognostic markers of disease outcome has yet to be established. In this study, we integrated somatic mutational profiles and clinicopathologic information from 544 gastric cancer patients from previous genomic studies to identify significantly mutated genes (SMG) with prognostic relevance.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 47 publications
5
118
0
3
Order By: Relevance
“…Genetic and epigenetic alterations play important role in GCs therefore, targeted therapy based on the biology of the individual patient could improve treatment outcome[17-19]. …”
Section: Introductionmentioning
confidence: 99%
“…Genetic and epigenetic alterations play important role in GCs therefore, targeted therapy based on the biology of the individual patient could improve treatment outcome[17-19]. …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we were unable to identify any mutations in seven patients using the Selective hotspot Panel, compared with only one using the Comprehensive Panel (Table 3). A recent study reported newly identified SMGs including NRG1 , ERBB4 , XIRP2 , NBEA , COL14A1 , CNBD1 , ITGAV , and AKAP6 [32, 33] that should be included in the mutational spectrum analyzed in all patients with gastric cancer. Second, from a cost perspective, covering more SMGs is beneficial, as shown by the comparable library preparation and sequencing running costs between the two panels used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer driver genes were obtained from 3 sources: (1) 16 gastric cancer‐related driver genes from Catalogue of Somatic Mutations in Cancer (COSMIC) Cancer Gene Census(v78)31; (2) 175 driver genes of gastric cancer from the Integrative Onco Genomics (IntOGen) database32; (3) 108 significantly mutated genes (SMGs) and 26 somatic copy number alteration genes from previously published Whole Genome Sequencing (WGS) or Whole Exome Sequencing (WES) articles 4, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22…”
Section: Methodsmentioning
confidence: 99%
“…DNA mismatch repair (MMR) genes were collected from 2 resources: identified MMR genes in a reported study and the genes in KEGG mismatch repair pathway 21. As a result, a total of 26 MMR genes were included in our analysis (Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation